Liver stiffness and associated risk factors among people with a history of injecting drugs: a prospective cohort study - Karl Trygve Druckrey-Fiskaaen; Jørn Henrik Vold; Tesfaye Madebo; Håvard Midgard; Olav Dalgard; Rafael Alexander Leiva; Lars T. Fadnes; for the INTRO-HCV Study Group (BMC, 2024)
Abstract Background Persons with opioid use disorders (OUD) and persons with substance use disorders (SUD) who inject substances have a reduced life expectancy of up to 25 years compared with the general population. Chronic liver diseases are a substantial cause of this. Screening strategies based on liver stiffness measurements (LSM) may facilitate early detection, timely intervention, and treatment of liver disease. This study aims to investigate the extent of chronic liver disease measured with transient elastography and the association between LSM and various risk factors, including substance use patterns, hepatitis C virus (HCV) infection, alcohol use, body mass index, age, type 2 diabetes mellitus, and high-density lipoprotein (HDL) cholesterol among people with OUD or with SUD who inject substances. Methods Data was collected from May 2017 to March 2022 in a cohort of 676 persons from Western Norway. The cohort was recruited from two populations: Persons receiving opioid agonist therapy (OAT) (81% of the sample) or persons with SUD injecting substances but not receiving OAT. All participants were assessed at least once with transient elastography. A linear mixed model was performed to assess the impact of risk factors such as HCV infection, alcohol use, lifestyle-associated factors, and substance use on liver stiffness at baseline and over time. Baseline was defined as the time of the first liver stiffness measurement. The results are presented as coefficients (in kilopascal (kPa)) with 95% confidence intervals (CI). Results At baseline, 12% (n = 83) of the study sample had LSM suggestive of advanced chronic liver disease (LSM ≥ 10 kPa). Advanced age (1.0 kPa per 10 years increments, 95% CI: 0.68;1.3), at least weekly alcohol use (1.3, 0.47;2.1), HCV infection (1.2, 0.55;1.9), low HDL cholesterol level (1.4, 0.64;2.2), and higher body mass index (0.25 per increasing unit, 0.17;0.32) were all significantly associated with higher LSM at baseline. Compared with persistent chronic HCV infection, a resolved HCV infection predicted a yearly reduction of LSM (-0.73, -1.3;-0.21) from baseline to the following liver stiffness measurement. Conclusions More than one-tenth of the participants in this study had LSM suggestive of advanced chronic liver disease. It underscores the need for addressing HCV infection and reducing lifestyle-related liver risk factors, such as metabolic health factors and alcohol consumption, to prevent the advancement of liver fibrosis or cirrhosis in this particular population.